Using 3D printing techniques to create an anthropomorphic thorax phantom for medical imaging purposes. Issue 1 (19th November 2017) - Hazelaar, Colien; van Eijnatten, Maureen; Dahele, Max; Wolff, Jan; Forouzanfar, Tymour; Slotman, Ben; Verbakel, Wilko F.A.R.
Abstract : Purpose: Imaging phantoms are widely used for testing and optimization of imaging devices without the need to expose humans to irradiation. However, commercially available phantoms are commonly manufactured in simple, generic forms and sizes and therefore do not resemble the clinical situation for many patients. Methods: Using 3D printing techniques, we created a life‐size phantom based on a clinical CT scan of the thorax from a patient with lung cancer. It was assembled from bony structures printed in gypsum, lung structures consisting of airways, blood vessels >1 mm, and outer lung surface, three lung tumors printed in nylon, and soft tissues represented by silicone (poured into a 3D‐printed mold). Results: Kilovoltage x‐ray and CT images of the phantom closely resemble those of the real patient in terms of size, shapes, and structures. Surface comparison using 3D models obtained from the phantom and the 3D models used for printing showed mean differences <1 mm for all structures. Tensile tests of the materials used for the phantom show that the phantom is able to endure radiation doses over 24, 000 Gy. Conclusions: It is feasible to create an anthropomorphic thorax phantom using 3D printing and molding techniques. The phantom closely resembles a real patient in terms of spatial accuracy and is currently being used to evaluate x‐ray‐based imaging quality and positional verification techniques for radiotherapy.